(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article investigates the pathoanatomical changes observed in poultry during the concurrent course of mycoplasmosis, colibacteriosis, and ornithobacteriosis. During the study, macroscopic pathological alterations in the respiratory system and internal organs of diseased poultry were analyzed. Necropsy findings revealed catarrhal-fibrinous tracheitis, aerosacculitis, pneumonia, pericarditis, perihepatitis, and dystrophic changes in internal organs. The formation of fibrinous exudate and caseous masses in the air sacs was identified as one of the characteristic pathological signs. It was established that the combined course of these diseases intensifies inflammatory processes in the organism and leads to more severe pathological manifestations. The obtained results are important for the diagnosis of mixed respiratory infections in poultry, deeper understanding of their pathogenesis, and the development of effective preventive and therapeutik measures.